The Diversity and Utilization of Weeds in Sengon (Falcataria moluccana (Miq.) Barneby & J.W.) Grimes) Agroforestry and Monoculture Pattern - Aji Winara; Endah Suhaendah (Balai Litbang Teknologi Agroforestry, Ciamis, 2020)
Sengon (Falcataria moluccana) is a superior commodity of private forests in Java island. However, its management faces a gall rust attack. In addition, another challenge is the presence of weed disturbance which can reduce plant growth productivity. This study aims to measure the diversity and utilization of weed species in the agroforestry and sengon monoculture demonstration plots. The research method used was the method of vegetation analysis of understorey and interviews. Data analysis was performed descriptively using the importance species index, species diversity index and species similarity index.The results showed that both cropping patterns produced the same level of diversity and species richness despite differences in species density and presence. A total of 29 species of weeds were found in the agroforestry pattern and 27 types in the monoculture pattern.. Weed species diversity in agroforestry and monoculture patterns is classified as moderate with Shannon-Wienner species diversity index (H ') values of 2.47 and 2.66 respectively. Likewise, the level of species richness both pattern is classified as moderate with Margalef Richness Index (R’) value of 3.89 in monoculture and 4.23 in agroforestry. The level of species similarity between the two cropping pattern according to the Bray-Curtis Index is 0.66. The density of weeds in the monoculture pattern is higher (66.00 individuals / m2) than the agroforestry pattern (62.25 individuals / m2). Most of the weeds (67.65%) are used by people around the forest as animal feed (18 species), foodstuffs (4 species) and traditional medicine (4 species). The many species of weeds that can be utilized by the community shows that sengon forests can support food security, so that the weed control techniques recommended are manual techniques with simple tools and spatial management with F. moluccana plants.